Feedlot performance by steers fed sprout-damaged milo - K.P. Coffey; Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1988)
Forty-eight Charolais crossbred steers were fed sprouted or nonsprouted milo for 139 days in a finishing study. Steers fed sprouted milo (51% sprout damage, 60 lb. per bu.) were 28 lb. heavier (P.10) feed per pound of gain. Sprout damaged milo had no significant (P>.10) effect on carcass characteristics. These data indicate that cattle fed sprouted milo should perform as well or better than those fed nonsprouted milo.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Feedlot performance; Steers; Sprout-damaged milo